Use of computed tomography in dimensional quality control and NDT - Beranek, Libor; Kroisova, Dora; Dvorackova, Stepanka; Urban, Jan; Simota, Jan; Andronov, Vladislav; Bures, Lukas; Pelikan, Lukas (Manufacturing Technology Journal, 2020)
The article deals with the application of computed tomography in dimensional quality control. The advantage of computed tomography is that the measured part is not influenced by measuring force. It is possible to measure complex parts and assemblies, their geometry, internal structure and defects in one step. The disadvantage of CT is decreasing accuracy and resolution when measuring hi density materials or larger parts, which leads to usage of high accelerating voltage and current. The measurement result is influenced by many factors, not only the instrument itself and the set of measuring parameters, but also largely depends on the sample itself, on its material and geometry. Based on the requirements for dimensional inspection, an analysis of the dependences of individual parameters of the Zeiss METROTOM 1500 computed tomography was conducted. The dependence of the spot size of the X-Ray source on the accelerating voltage and current was determined for the given instrument, as well as the relation between the voxel size and the distance of the sample from the detector. Spot size and voxel size has to be in relation, since large spot size goes against high magnification, high resolution meaning small voxel size. Using calibration artefact, the influence of the acceleration voltage on the accuracy when measuring form and size of a sphere and the distance between centres of 2 spheres was evaluated.
Keywords: Computed tomography; Voxel size; Spot size